Pendidikan Remaja Sadar Test Anti Napza (PRESTASI): Edukasi dan Pendampingan: Adolescent Education on Anti-Drug Awareness Test (PRESTASI): Education and Mentoring - Prihatiningsih, Diah; Bintari, Ni Wayan Desi; Widana, Anak Agung Gde Oka; Purwanti, Ika Setya (Chakra Brahmanda Lentera Institute, 2026)
Drug and addictive substance abuse (NAPZA) among adolescents continues to rise and brings serious consequences—ranging from physical and mental health problems to impaired social relationships and academic performance. In response to this issue, the community service program Pendidikan Remaja Sadar Tes Anti NAPZA (PRESTASI) was implemented at SMA PGRI 4 Denpasar to strengthen students’ knowledge, attitudes, and awareness regarding the dangers of NAPZA and the importance of early detection. This program employed a one-group pre-test–post-test design. A total of 30 students participated, with 10 students selected as peer educators. The activities included interactive lectures, group discussions, peer educator role-play simulations, and demonstrations on the use of rapid urine test kits. Changes in knowledge were measured using a 10-item multiple-choice questionnaire administered before and after the program. The results showed a clear improvement in knowledge: in the post-test, all participants (100%) achieved a “good” knowledge category, up from 26.67% in the pre-test. In addition, students demonstrated high enthusiasm during the rapid urine test demonstration session and expressed readiness to actively serve as peer educators in school-based prevention efforts. Overall, the PRESTASI program proved effective in improving students’ knowledge while strengthening the role of peer educators as health promotion agents within the school environment. Going forward, the program is recommended to be integrated into School Health Unit (UKS) activities and reinforced through collaboration with the National Narcotics Board (BNN) and other relevant stakeholders to ensure sustainable education and early detection initiatives.